Trauma Patients' Attitudes toward Organ Donation at an Urban Level I Trauma Center. Issue 9 (September 2018) - Cull, John D.; Ivkovic, Katarina; Manning, Benjamin; Chan, Edie Y.
Many health-care workers (HCWs) surveyed at a trauma center believed their patients distrusted the organ allocation system. This study compares urban trauma patients' (TPs) attitudes toward organ donation with attitudes from the 2012 National Survey of Organ Donation Attitudes (NSODA). TPs presenting to the trauma clinic between September 2014 and August 2015 were surveyed. Patient responses were compared with the 2012 NSODA. One hundred and thirty-three TPs (95.0%) responded to the survey. Compared with the 2012 NSODA, groups were similar with regard to a patient's desire for OD after death (Trauma: 62.4% [Confidence interval [CI]: 53.6–70.7] vs NSODA: 59.3% [CI: 56.6–61.8]) and the belief that doctors are less likely to save their life if they are an organ donor (24.8% [CI: 17.7–33.0] vs 19.6% [CI: 18.3–21.0]). Approximately, 30 per cent of patients believed discrimination prevented minority patients from receiving transplants (27.1 [CI: 19.7–35.5] vs 30.3 [CI: 28.8–31.9]). TPs were less likely than the NSODA group to donate a family members' organs, if they did not know the family members' wishes (56.4% [CI: 47.5–65.0] vs 75.6% [CI: 68.7–71.8]); TPs were less likely to believe the United States transplant system uses a fair approach to distribute organs (47.4% [38.7–56.2] vs 64.6% [CI: 63.0–66.2]). Adjusting for race, both groups were similar in their willingness to donate a family members' organs; black TPs were less likely to believe the United States transplant system, which follows a fair approach in distributing organs (43.0% [CI: 32.4–54.2] vs 63.7% [59.7–67.6]). Despite HCWs perceptions, TPs had a positive view of OD. Educating HCWs on patient attitudes toward OD may decrease institutional barriers to OD.